Pertumbuhan dan Produksi Dua Varietas Tanaman Tomat terhadap Beberapa Konsentrasi Kolkhisin - Ariani Syahfitri Harahap (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2019)
Indonesia has decreased tomato production so that it cannot meet the needs of the community. Therefore, innovation is needed to meet the increasing needs of tomatoes. One way is to form polyploid plants using colchicines. In this research a factorial randomized block design (RAK) was used with two treatments, namely Varieties (Servo F1 and Gem) and Colchhisin Concentration (0, 0.1% and 0.2%) with 4 replications with a total plant total of 24 polibek. Immersion is carried out for 6 hours. Plant height, number of leaves, number of branches, number of flowers, number of fruits per plant and weight of fruits per plant were observed parameters. From the results of the analysis showed that the variety and concentration of kolchhisin did not significantly affect all parameters. Therefore, further research will be carried out to obtain the right concentration in forming polyploid tomato plants